Association between neck circumferences and cardiometabolic risk factors - Bendigeri, Mukhtarahmed; Akbar, Ali; Reddy, Dheeraj Kumar; Jaladhar, Prakruthi (International Journal of Advances in Medicine, 2019)
Background: Anthropometric measures have been used for screening patients for cardiovascular abnormalities and metabolic syndrome since many years. There are numerous methods to assessing overweight and obesity, such as measurements of weight, height, waist circumference, hip circumference and calculation of waist hip ratio and BMI. Due to cultural inhibitions measurement of hip, thigh or waist circumference is cumbersome in females, neck circumference could be an acceptable option for such patients. Methods: A cross-sectional study was conducted on patients attending the outpatient department in Yenepoya medical college Hospital between the period of May 2017 to May 2018. Total 201 patients chosen randomly in which 145 males and 56 females, fulfilling criteria of age >20 years were included. Pregnant females, patients with thyroid disorders, history of previous neck surgery were excluded. Results: Out of the 201 population studied, Cardio metabolic syndrome was present in 94 participants according to criteria of NCEP ATP III. In our study there is a significant correlation between neck circumference and metabolic syndrome (p value <0.001). Conclusions: Patients with Neck Circumference (NC) >37 cm in males and >34 cm in females are more prone for having cardio metabolic risk factors than patients with NC <37 cm in males and <34 cm in females. NC may be used as a simple and time saving screening measure to identify cardio metabolic risk factors in patients.